1992 [videorecording (Blu-Ray + DVD)] - Vromen, Ariel, 1973-; Penn, Sascha; Tyrese; Liotta, Ray; Bennett, Clé; Arnold, Dylan; Eastwood, Scott, 1986- (Lionsgate, 2024)
In 1992, Mercer is desperately trying to rebuild his life and relationship with his son amidst the turbulent 1992 LA uprising following the Rodney King verdict. Across town, another father and son put their own strained relationship to the test as they plot a dangerous heist to steal catalytic converters, which contain valuable platinum, from the factory where Mercer works. As tensions rise in Los Angeles and chaos erupts, both families reach their boiling points when they collide.